SECTARIANIZING GEOPOLITICS: Responses of Indonesian Muslims to the 2026 US-Israel vs. Iran War - Ahmad Khoirul Fata; Slamet Muliono Redjosari; Rifki Abror Ananda (TANFIDZIY, 2026)
The open warfare between the US-Israel alliance and Iran in early 2026 not only escalated Middle Eastern geopolitics but also triggered a sharp theological polarization in Indonesia. This study aims to analyze how this transnational geopolitical conflict was domesticated and constructed into a religious cleavage within Indonesia's digital sphere. Utilizing a qualitative approach framed by Raymond Hinnebusch’s sectarianization theory and conflict theory, this article dissects the narrative responses of two main factions in Indonesia. The findings reveal a stark fragmentation of religious authority. On one hand, mainstream Islamic organizations (PBNU, Muhammadiyah, and MUI) employed the lenses of international law and universal humanitarian solidarity, rooted in institutional-procedural authority. On the other hand, popular digital preachers utilized a puritan-Salafi approach, framing the conflict exclusively through internal theological (aqeedah) doctrines, collective memories of anti-Shia sentiments, and end-times narratives. Social media functioned as an identity reinforcement machine, accelerating the transition from geopolitical analysis to theological judgment. The implications of this polarization not only erode social cohesion and threaten the domestic Shia minority through local boundary making but also marginalize the core Palestinian solidarity. This study underscores the critical need for public maturity in separating global geopolitical dynamics from domestic sectarian manipulation.